Blockchain Implementation in the Development of a Zero Trust-Based Cybersecurity Framework at the Indonesian National Data Center - Khair, Rizaldy; Lubis, Hamidah Azzahrah S; Vickri Febrian (Universitas Budi Darma, 2025)
Indonesia's National Data Center (PDN) has a strategic role in the country's digital infrastructure, but it is a potential target for cyberattacks. Conventional security models have proven inadequate in dealing with the complexity of modern threats, so a Zero Trust Architecture (ZTA) approach is necessary. This research aims to develop a Zero Trust security framework that is integrated with blockchain technology to improve the efficiency and resilience of PDN systems. The research methods include literature study, identification of PDN security needs, framework design, prototype development using Hyperledger Fabric, and testing and evaluation in a simulation environment. The framework built consists of blockchain-based identity verification, minimum access control (least privilege), and blockchain-based activity monitoring and logging. Provisional results show that the framework successfully rejects 98% of simulated internal attacks, reduces the success of unauthorized access by 80%, and reduces the success of phishing attacks from 25% to 5%. A survey of administrators showed that 90% said security improvements and 85% said the system remained user-friendly. While providing significant improvements in security and auditability, this framework creates an additional latency of 100–150 ms and demands expert human resources. This research contributes to the development of a more transparent and resilient national security model through the integration of blockchain and Zero Trust principles.